Comparison of oven dried and freeze dried orally disintegrating film (ODF) formulations containing memantine hydrochloride - Phang, Hiu Ching; Tan, Julia M; Subramaniam, Poonguzhali; Helal Uddin, A.B.M.; Ee, Mei Hooi; Lakshminarayanan, Vijayakumar; Liew, Kai Bin (International Journal of Pharmaceutical Compounding, Inc., 2024)
Non-compliance is a serious healthcare issue. It contributes to waste of medication, deterioration of patient’s quality of life and increase in healthcare cost. It is challenging to ensure Alzheimer's disease patients to comply to their medication daily. Hence, patient friendly and innovative dosage form is required to overcome the challenges. Orally disintegrating film (ODF) is proposed as solution to non-compliance. The objective of this research was to compare oven drying and freeze drying process on the physical properties of memantine hydrochloride ODF. A central composite design was used. The factors considered were concentration of Guar Gum (0.5–1.84g), concentration of wheat starch (0.5–1.84g) and concentration of PEG 400 (0.5–1.84g). A total of 20 formulations for each drying method were prepared. The ODFs produced were then characterized using uniformity of thickness tensile strength, folding endurance, disintegration time test. The optimum formulation was selected and incorporated with memantine hydrochloride. A flexible Memantine hydrochloride ODF formulation with fast disintegration time, sufficient mechanical strength and stable over a period of six months was successfully developed. The optimum formulation has 1.50 g guar gum, 1.50 g starch and 1.50 g of PEG 400. Freeze dried films are preferred as these films are more flexible and porous that lead to faster disintegration time. The findings suggest that memantine hydrochloride ODF has the potential as an alternative dosage form in treating Alzheimer’s disease.